The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1245/s10434-009-0542-1
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Prophylactic Antibiotics and Surgical Site Infection Rates in Breast Surgery Patients

Abstract: Although the overall number of patients who developed SSI was relatively small, there was no reduction in the SSI rate among those who received postoperative antibiotic prophylaxis. Because of the potential adverse events associated with antibiotic use, further evaluation of this practice is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 30 publications
0
61
1
Order By: Relevance
“…1042,1043 Most dermatological, breast (reduction and reconstructive), clean head and neck, and facial procedures have an associated SSI rate of <5%. [1044][1045][1046][1047][1048][1049][1050][1051][1052][1053] Oral procedures, such as wedge excision of lip or ear, flaps on the nose, 1046,1054 and head and neck flaps, have SSI rates of approximately 5-10%. 1053,[1055][1056][1057][1058][1059][1060] In addition to general risk factors as described in the Common Principles section, factors that increase the risk of postoperative infectious complications for plastic surgery procedures include implants, 1061 skin irradiation before the procedure, and procedures below the waist.…”
Section: Plastic Surgery and Breast Proceduresmentioning
confidence: 99%
“…1042,1043 Most dermatological, breast (reduction and reconstructive), clean head and neck, and facial procedures have an associated SSI rate of <5%. [1044][1045][1046][1047][1048][1049][1050][1051][1052][1053] Oral procedures, such as wedge excision of lip or ear, flaps on the nose, 1046,1054 and head and neck flaps, have SSI rates of approximately 5-10%. 1053,[1055][1056][1057][1058][1059][1060] In addition to general risk factors as described in the Common Principles section, factors that increase the risk of postoperative infectious complications for plastic surgery procedures include implants, 1061 skin irradiation before the procedure, and procedures below the waist.…”
Section: Plastic Surgery and Breast Proceduresmentioning
confidence: 99%
“…In order to prevent the development of side effects and resistance, antimicrobial prophylaxis should be discontinued as soon as possible even if drains, catheters or implants have been used in breast and plastic surgery operations (4,5,11,16,19,28). In breast surgery, any significant differences were not found between single dose antimicrobial prophylaxis regimens and extended protocols in terms of wound infection (5,11,19).…”
Section: Duration Of Prophylaxismentioning
confidence: 99%
“…The risk of wound infection is below 5% in surgical procedures including breast reduction and reconstruction surgery, in a patient without additional risk factors for infection (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In addition to patient specific conditions that are known to increase the risk of infection in all kinds of surgical wounds in general, the use of implants in breast surgery (13) and preoperative radiotherapy application (14,15) further increase the risk of wound infection.…”
Section: Introductionmentioning
confidence: 99%
“…In the sole supportive study, Throckmorton et al demonstrated no difference in surgical-site infection between patients following elective breast surgery in which the Surgical Care Improvement Project protocol was or was not followed. 7 The majority of patients in this study did not have breast reconstruction. Of the two nonsupportive studies, Berhane et al demonstrated that following prosthetic reconstruction with acellular dermal matrix, the incidence of surgical-site infection was 31.3 percent when only intravenous antibiotics were administered.…”
mentioning
confidence: 91%